Effects of postglacial seawater intrusion on sediment geochemical characteristics in the Romanian sector of the Black Sea. (January 2021) - Ruffine, Livio; Deusner, Christian; Haeckel, Matthias; Kossel, Elke; Toucanne, Samuel; Chéron, Sandrine; Boissier, Audrey; Schmidt, Mark; Donval, Jean-Pierre; Scholz, Florian; Guyader, Vivien; Ker, Stéphan; et al.
Abstract: Pore water and sediment geochemistry in the western Black Sea were investigated on long Calypso piston core samples. Using this type of coring device facilitates the recovery of the thick sediment record necessary to analyze transport-reaction processes in response to the postglacial sea-level rise and intrusion of Mediterranean salt water 9 ka ago, and thus, to better characterize key biogeochemical processes and process changes in response to the shift from lacustrine to marine bottom water composition. Complementary data indicate that organic matter degradation occurs in the upper 15 m of the sediment column. However, sulfate reduction coupled with Anaerobic Methane Oxidation (AOM) is the dominant electron-accepting process and characterized by a shallow Sulfate Methane Transition Zone (SMTZ). Net silica dissolution, total alkalinity (TA) maxima and carbonate peaks are found at shallow depths. Pore water profiles clearly show the uptake of K+, Mg2+ and Na + by, and release of Ca2+ and Sr2+ from the heterogeneous lacustrine sediments, which is likely controlled by chemical reactions of silicate minerals and changes in clay mineral composition. Iron (Fe2+) and manganese (Mn2+) maxima largely coincide with Ca2+ peaks and suggest a close link between Fe2+, Mn2+ and Ca2+ release. We hypothesize that the Fe2+ maxima below the SMTZ result from deep Fe3+ reduction linked to organic matter degradation, either driven by DOC escaping from the shallow sulfate reduction zone or slow degradation of recalcitrant POC. The chemical analysis of dissolved and solid iron species indicates that iron is essentially associated with clay minerals, which suggests that microbial iron reduction is influenced by clay mineral composition and bioavailability of clay mineral-bound Fe(III). Overall, our study suggests that postglacial seawater intrusion plays a major role in shaping redox zonation and geochemical profiles in the lacustrine sediments of the Late Quaternary. Highlights: Geochemical analyses highlight multiple diagenesis processes occurring in the sediment. Intense methane seepages and organic matter degradation contribute to the sulfate reduction. Chemical of dissolved and mineral iron species indicate that iron is associated with clay minerals. In response to seawater intrusion, ion exchange, dissolution and reverse weathering reactions change the composition of clay constituting the sediment.